Civil legal relations in the context of adaptation of civil legislation to the legislation of the EU countries in the digital age - Kizlova, Olena; Safonchyk, Oksana; Hlyniana, Kateryna; Mazurenko, Svetlana (My University, 2021)
An essential area is the creation of a single digital market between the EU and Ukraine through information technology. Purpose: to investigate and analyze civil law relations in the field of adaptation of Ukrainian civil law to civil law regulations of the EU. The object of research: Ukrainian civil law and civil law of the EU. The subject of the study is civil law in the context of adaptation of civil law to the legislation of the EU. The following methods of scientific cognition were used during the research: semantic, historical, comparison, analysis and synthesis, generalization. The results of the study show that the harmonization of the legal system of Ukraine with EU law is caused by several goals: successful integration of Ukraine into the EU, legal reforms based on the positive example of EU countries, promoting access of Ukrainian enterprises to the EU market; attracting foreign investment, increasing the welfare of Ukrainian citizens. The adaptation includes three stages, the final of which is the preparation of an expanded program of harmonization of Ukrainian legislation with EU legislation. In the process of adaptation, it is important to take into account the legal history, tradition, features and mentality of Ukraine and before borrowing legal structures to analyze the feasibility of their application in the Ukrainian legal field.
Kizlova Olena Civil legal relations in the context of adaptation of civil legislation to the legislation of the EU countries in the digital age / Olena Kizlova, Oksana Safonchyk, Kateryna Hlyniana, Svetlana Mazurenko // International Journal of Computer Science and Network Security. - 2021. – Vol. 21, № 12. - P. 521-525.
Keywords: Digital single market; information technologies; adaptation of civil legislation; European integration; harmonization of legislation